2017
DOI: 10.3759/tropics.ms16-15
|View full text |Cite
|
Sign up to set email alerts
|

Variations on growth characteristics and wood properties of three <i>Eucalyptus</i> species planted for pulpwood in Indonesia

Abstract: Fast-growing tree species are being considered as an alternative source of timber to augment the supply in southern Asian countries. Eucalyptus is one of the most promising genus because its fast-growing characteristics and hybridization among species can produce superior characteristics valuable to both the pulp and timber industries. To evaluate the possibility of using it for timber, growth characteristics and wood properties were investigated for three nine-year-old Eucalyptus species (E. urophylla, E. gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
6
14
1
2
Order By: Relevance
“…E. pellita wood has physical and chemical properties in the form of holocellulose content (75%), alpha-cellulose (49%), lignin content (29%), ethanol content (3.08%), and fiber length of 1.02 mm (Lukmandaru et al 2016) suitable as raw material for pulp and paper industry. E. pellita shows the characteristics of well growing and prominent wood characteristic compare to the other two species, namely E. grandis and E. urophylla (Prasetyo et al 2017). Investment and expansion in Eucalyptus plantations and pulp mills is predicted to continue sustainably (Phillips 2013).…”
Section: Introductionmentioning
confidence: 99%
“…E. pellita wood has physical and chemical properties in the form of holocellulose content (75%), alpha-cellulose (49%), lignin content (29%), ethanol content (3.08%), and fiber length of 1.02 mm (Lukmandaru et al 2016) suitable as raw material for pulp and paper industry. E. pellita shows the characteristics of well growing and prominent wood characteristic compare to the other two species, namely E. grandis and E. urophylla (Prasetyo et al 2017). Investment and expansion in Eucalyptus plantations and pulp mills is predicted to continue sustainably (Phillips 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In 9-year-old E. camaldulensis trees grown in Thailand, the basic density was 0.66 g/cm 3 (Veenin et al, 2005). For 9-year-old E. urophylla, E. grandis, and E. pellita trees planted in Indonesia, the mean values of the basic density were 0.46, 0.41, and 0.46 g/cm 3 , respectively (Prasetyo et al, 2017). Dickson et al (2003) reported that the basic density of 25-yearold E. dunnii trees planted in Vietnam was 0.60 g/cm 3 .…”
Section: Wood Propertiesmentioning
confidence: 94%
“…The mean values of stress-wave velocity in the present study was 3.44 km/s (Table 2). Several researchers have measured the stress-wave velocity of stems in Eucalyptus species at an age of approximately 10 years old or older (Blackburn et al, 2010;Wahyudi et al, 2015;Prasetyo et al, 2017). Blackburn et al (2010) reported that the stress-wave velocity of the stem ranged from 3.18 to 3.36 km/s in 14-year-old E. nitens trees planted in Australia.…”
Section: Wood Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil pengukuran kerapatan kayu klon E. pellita pada penelitian ini berkisar pada rentang 404,5 -558,7 kg m -3 (Tabel 1). Hasil tersebut searah dengan hasil Penelitian Prasetyo et al (2017) yang menyebutkan kerapatan kayu E. pellita adalah 460 (400 -550) kg m -3 pada umur 9 tahun di Sumatera utara. Rentang yang hampir sama ditemui pada Kerapatan kayu klon-klon Eucalyptus hibrid di Cina umur 5,5 tahun yaitu 468 -483 kg m -3 sesuai hasil penelitian Luo et al (2012) dan 404 -427 kg m -3 pada umur 51 bulan (Wu et al, 2015).…”
Section: Pertumbuhanunclassified